Law No. 157/1981 Promulgating Income Tax Law = قانون الضرائب رقم 157 لسنة 1981 المعدل بالضريبة الموحدة - Egypt (2025)
PART 1 Movable / Movable Capitals Revenues Chapter: 1 Taxable Revenue Chapter: 2 Determination of Revenues Falling within the Tax Assessment Bracket. Chapter: 3 Exemption from the Tax Chapter:4 Collection of Tax. PART II Revenues of Commercial and Industrial Activity Chapter: 1 Taxable Revenues. Chapter: II Determination of Revenues Entering in Tax Assessment Bracket. Chapter1: Chapter: IV Deduction, Addition and Collection for Ill Exemption from the Tax Account of the Tax PART-3 Salaries and Payments of Like Status Chapter: 1 Taxable Revenues Chapter2: 2 Determination of Revenues Forming Part of the Tax Assessment Bracket. from the Tax. Chapter: 3 Exemption Chapter: 4 Declarations Section-1 Declarations to be submitted by the Employer......... Section-2 Declarations to be submitted by the Salaried /Work Income Earners. Chapter 5 Collection of the Tax. Chapter: 6 Objection and Contestation PART-4 Revenues of Non-Commercial Professions Chapter: 1 Taxable Revenues. Chapter: 2 Determination of Revenues Entering in the Tax Assessment Bracket Chapter: 3 Tax Exemption Chapter: 4 Taxpayer's Obligations. Chapter: 5 Deduction and Collection for Account of the Tax........ 45 PART-5 Revenues of Real Estate Wealth Chapter: I Assessable/Taxable Revenues. Chapter: 2 Determination of Revenues Placed Under the Tax Assessment Bracket. Chapter: 3 Collection for Account of the Tax Chapter: 4 Different Provisions PART-6 General Provisions Chapter: 1 Exemption from the Tax. Chapter: 2 Rate of the Tax. Chapter: 3 Declarations and Books